Peran Inspeksi Diri dalam Menjamin Mutu Distribusi Obat: Studi Kasus pada Beberapa Pedagang Besar Farmasi - Suspa Nita, Rina; Jariyah, Ainun; Latipah, Nor (STIKes Ibnu Sina Ajibarang, 2025)
This review explores the role of self-inspection in maintaining the quality of drug distribution, with a specific focus on case studies involving several pharmaceutical wholesalers (Pedagang Besar Farmasi). The objective is to evaluate how self-inspection is implemented, identify common obstacles, and assess its effectiveness in ensuring compliance with Good Distribution Practices (GDP). Through a qualitative analysis of selected literature and documented practices within Indonesian pharmaceutical wholesalers, the study finds that consistent and well-documented self-inspections can significantly improve operational quality, support regulatory compliance, and mitigate distribution risks. However, gaps in personnel competency, irregular inspection schedules, and limited follow-up actions are recurring challenges. The review emphasizes the need for stronger internal audit frameworks, management commitment, and regulatory guidance to optimize the role of self-inspection as a quality assurance tool in pharmaceutical distribution.